Anti-interference low-temperature wear-resistant POP laminating film
By setting up a hemispherical structure with a staggered height in the prism layer structure of the POP bonding film and using low-temperature wear-resistant resin, the problem that the POP bonding film is prone to interference fringes on high-resolution TV screens and easily scratches the liquid crystal screen at low temperatures is solved, and the effect of improving interference fringes and reducing wear risks is achieved.
Patent Information
- Application Number
- CN202411904040.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-02-28
AI Technical Summary
The existing POP patch film is prone to interference fringes on high-resolution TV screens, and easily scratches the lower polarizer of the LCD screen under low temperature environments.
The improved upper prism layer structure is adopted. The cross-section of the prism is a triangular structure with an arc-shaped top, and a hemispherical structure with a staggered height and low height are set on the prism peaks, and a low-temperature wear-resistant resin is used as the material.
The appearance of interference fringes is significantly improved, reducing the risk of wear on the polarizer under the LCD screen in low temperature environments, while not affecting the performance of POP.
Smart Images

Figure CN119535659A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of screen laminating films and relates to an interference-resistant, low-temperature and wear-resistant POP laminating film. Background Art
[0002] With the popularization of TFT-LCD liquid crystal display technology, the demand for its backlight module and related optical films has increased, and the cost requirements have become increasingly stringent. The four-film structure of lower diffusion, 90-degree light enhancement, 0-degree light enhancement, and upper diffusion previously used has been gradually replaced by three or even two films. With the increasing size, the requirements for stiffness have become higher, the products have been continuously thinned, and the assembly line has become more and more simplified for film assembly. DOP (light enhancement + diffusion), MOP (light enhancement + Microlens) and POP (light enhancement + light enhancement) laminated films have also appeared on the market. POP is a product with higher performance (brightness) than MOP and DOP. Its brightness, shielding, and cost are ranked as follows: brightness POP>MOP>DOP, shielding DOP>MOP>POP, and cost POP=MOP>DOP. As the national energy consumption requirements are gradually increasing, the advantages of POP highlighting have become more and more obvious, and POP has begun to become popular in the market.
[0003] However, as TV resolution increases and 4K and 8K TVs become more popular, the defect of poor shielding caused by the structure of POP (prism structure on both the top and bottom) becomes more obvious, and it is more prone to interference (interference with the pixels of the TV screen), forming thick strips or ring-shaped interference fringes. In addition, the surface of POP is a prism structure (similar to a sawtooth structure), which can easily scratch the lower polarizing layer of the LCD panel, especially in low temperature environments (below -30°C). It is because of the surface structural characteristics of POP that it is difficult to promote and use in cold areas. Summary of the invention
[0004] The purpose of the present invention is to solve the defects of the prior art, improve the defects of the POP structure that interference fringes are easily generated, and the surface ultraviolet curing resin at low temperature is easy to scratch the lower polarizer of the liquid crystal screen under low temperature conditions, and provide an anti-interference low-temperature wear-resistant POP laminating film that improves interference fringes without affecting the performance of POP and is not easy to scratch the lower polarizer of the liquid crystal screen at low temperature. The improvement of the POP laminating film of the present invention is that the upper surface prism structure is improved and the improved UV resin is used.
[0005] On one hand, the present invention provides a POP laminating film, which is divided into two layers, namely a structural layer (lower prism layer) and an upper prism layer from bottom to top, wherein the structural surface of the structural layer (lower prism layer) and the bottom surface of the upper prism layer are bonded by composite adhesive.
[0006] The prisms of the upper prism layer are arranged in a row, and the cross section of the prism is a triangular structure with an arc-shaped top. The peak (prism peak) of the top of a single prism of the upper prism layer is composed of a number of hemispherical structures of different sizes arranged in a certain order, forming a special structure of staggered heights.
[0007] The structural layers are arranged in a columnar manner and have a triangular cross-section. The configuration of the structural layers is consistent with that of ordinary POP laminating films.
[0008] In some preferred embodiments, the prism pitch of the upper prism layer is 15 to 28 microns, and the height of the prism is generally half of the prism pitch, i.e., 7 to 14 microns. In some more preferred embodiments, the prism pitch of the upper prism layer is 18 to 20 microns, and the height is 9 to 10 microns.
[0009] In some preferred embodiments, the angle corresponding to the top arc of the cross section of the prism-like triangular structure is 88° to 90°, and the diameter of the corresponding circle is 0.5 to 1 micron. This arc structure can prevent the peak of the upper prism layer (similar to a sawtooth structure) from easily scratching the lower polarized light of the liquid crystal panel.
[0010] In some preferred embodiments, a number of small hemispherical structures are distributed between every two large hemispherical structures of the prism peaks; the span of each large hemispherical structure is A (50 to 500 microns) and the height is D (5 to 10 microns); the span of each small hemispherical structure is C (10 to 100 microns) and the height is 1 / 5D (1 to 2 microns); the spacing between each large hemispherical structure is B, and B = n*C, where n is a positive integer of 5 to 10.
[0011] The prism layer on the POP laminating film of the present invention has a special structure of staggered heights. Each prism peak is composed of a large jitter (i.e., a large hemispherical structure) + a plurality of small jitters (i.e., a small hemispherical structure). The small hemispherical structure can reduce the risk of interference. The smaller the span and peak height of the small hemispherical structure, the lower the risk of interference. The large hemispherical structure can reduce the contact area between the prism peak and the polarizer under the upper screen.
[0012] In some preferred embodiments, the prisms of the upper prism layer are made of low-temperature wear-resistant resin and are prepared from the following components in parts by weight:
[0013] 5-10 parts of monomer (ethoxylated bisphenol A diacrylate resin) and 25-30 parts of initiator (4-(phenylthio)phenyl diphenylsulfonium hexafluoroantimonate) are dispersed at high speed of 500-2000 r / min in a dark environment. After dispersion for 30 minutes, 15-20 parts of the first type of acrylic resin (o-phenylphenoxyethyl acrylic resin or ethoxylated o-phenylphenoxyethyl acrylic resin), 25-30 parts of the second type of acrylic resin (phenol acrylic resin or ethoxylated phenol acrylic resin) and 5-10 parts of oligomer (polyurethane acrylic or epoxy acrylic resin) are added, heated to 30-40°C in a dark environment and continued to disperse at high speed of 500-2000 r / min for 30 minutes. Finally, 0.5-1 part of a slip agent is added, heated to 30-40°C and continued to disperse at high speed of 500-2000 r / min for 60 minutes. After passing through a filtration system, a low-temperature wear-resistant resin is obtained.
[0014] The stirring speed of the high-speed dispersion is sufficient to achieve uniform mixing, preferably 1200 r / min. In some preferred embodiments, the stirring time can be further shortened or extended to 20-60 min.
[0015] In some preferred embodiments, the filtration system specifically refers to filtering the uniformly mixed solution through a 0.5 micron filter bag and a 0.1 micron filter element.
[0016] The present invention adopts the above-mentioned low-temperature wear-resistant resin as the prism material of the upper prism layer. The upper prism layer is made by using a conventional PET surface rolling process.
[0017] The currently commonly used POP laminating film structure is prone to interference with the pixels of the TV screen, forming thick long strips or ring-shaped interference fringes. The POP laminating film of the present invention adopts a specially designed upper prism layer prism structure, and by setting a number of small spherical structures on the prism peaks, the interference fringes can be significantly improved without affecting the POP performance. Secondly, the present invention further solves the defect that the POP laminating film is easy to scratch the lower polarizer of the liquid crystal screen. The present invention sets the top of the prism of the upper prism layer into an arc shape, and sets multiple groups of large spherical structures on the prism peaks, and uses low-temperature wear-resistant resin as the prism material, which can significantly reduce the risk of scratches. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The figure shows a schematic cross-sectional view of the prism of the upper prism layer of the POP laminating film of the present invention;
[0019] Figure 2 Shown is a schematic structural diagram of the upper prism layer of the POP laminating film of the present invention;
[0020] Figure 3The figure shows a schematic diagram of the side projection structure of the prism peaks of the upper prism layer of the POP laminating film of the present invention;
[0021] Figure 4 The structure diagram of the POP laminating film of the present invention is shown;
[0022] Figure 5 Shown is a schematic diagram of interference fringes of a common POP laminating film in Test Example 2;
[0023] Figure 6 Shown is a schematic diagram of interference fringes of the POP laminating film of the present invention in Test Example 2;
[0024] Figure 7 Shown is a schematic diagram of the structure of the DOP laminating film;
[0025] Figure 8 Shown is a schematic diagram of the structure of the MOP laminating film. DETAILED DESCRIPTION
[0026] In order to further understand the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0027] The term "POP laminating film" used in this article refers to Prism ON Prism, that is, a composite film in which a micro-transparent structural film and a prism are laminated together. Generally, the POP laminating film is composed of a structural layer (lower prism layer) and an upper prism layer from bottom to top, and the structural surface of the structural layer (lower prism layer) and the back surface of the prism layer are bonded by composite adhesive.
[0028] The invention provides a POP laminating film, which is divided into two layers, namely a structural layer (lower prism layer) and an upper prism layer from bottom to top, wherein the structural surface of the structural layer (lower prism layer) and the bottom surface of the upper prism layer are bonded by composite adhesive.
[0029] like Figure 1 As shown, the prisms of the upper prism layer are arranged in a row, and the cross section of the prism is a triangular structure with an arc-shaped top. Figure 2 As shown, the peak (prism peak) at the top of a single prism of the upper prism layer is composed of a number of hemispherical structures of different sizes arranged in a certain order, forming a special structure of staggered heights. The prism described in the present invention is specifically columnar, and its cross section is a triangular-shaped cross section with an arc-shaped top, and due to the different sizes of hemispherical structures, the top heights of the cross sections of different parts of the prism will be different.
[0030] The structural layers are arranged in a columnar manner and have a triangular cross-section. The configuration of the structural layers is consistent with that of ordinary POP laminating films.
[0031] In some preferred embodiments, the prism pitch of the upper prism layer is 15 to 28 microns, and the structure height is 7 to 14 microns. In some more preferred embodiments, the prism pitch of the upper prism layer is 18 to 20 microns, and the structure height is 9 to 10 microns.
[0032] In some preferred embodiments, the angle corresponding to the top arc of the cross section of the prism-like triangular structure is 88° to 90°, and the diameter of the corresponding circle is 0.5 to 1 micron. This arc structure can prevent the peak of the upper prism layer (similar to a sawtooth structure) from easily scratching the lower polarized light of the liquid crystal panel.
[0033] In some preferred embodiments, the ridge peak structure is as follows Figure 3 As shown, there are several small hemispherical structures distributed between every two large hemispherical structures; the span of each large hemispherical structure is A (50-500 microns) and the height is D (5-10 microns); the span of each small hemispherical structure is C (10-100 microns) and the height is 1 / 5D (1-2 microns); the spacing between each large hemispherical structure is B, and B=n*C, n is a positive integer of 5-10.
[0034] The prism layer on the POP laminating film of the present invention has a special structure of staggered heights. Each prism peak is composed of a large jitter (i.e., a large hemispherical structure) + a plurality of small jitters (i.e., a small hemispherical structure). The small hemispherical structure can reduce the risk of interference. The smaller the span and peak height of the small hemispherical structure, the lower the risk of interference. The large hemispherical structure can reduce the contact area between the prism peak and the polarizer under the upper screen.
[0035] In some preferred embodiments, the prisms of the upper prism layer are made of low-temperature wear-resistant resin and are prepared from the following components in parts by weight:
[0036] 25-30 parts of monomer (ethoxylated bisphenol A diacrylate resin) and 1-3 parts of initiator (4-(phenylthio)phenyl diphenylsulfonium hexafluoroantimonate) are dispersed at high speed of 500-2000 r / min in a dark environment. After dispersion for 30 minutes, 15-20 parts of the first type of acrylic resin (o-phenylphenoxyethyl acrylic resin or ethoxylated o-phenylphenoxyethyl acrylic resin), 25-30 parts of the second type of acrylic resin (phenol acrylic resin or ethoxylated phenol acrylic resin) and 5-10 parts of oligomer (polyurethane acrylic or epoxy acrylic resin) are added, heated to 30-40°C in a dark environment and continued to disperse at high speed of 500-2000 r / min for 30 minutes. Finally, 0.5-1 part of a slip agent is added, heated to 30-40°C and continued to disperse at high speed of 500-2000 r / min for 60 minutes. After passing through a filtration system, a low-temperature wear-resistant resin is obtained.
[0037] The stirring speed of the high-speed dispersion is sufficient to achieve uniform mixing, preferably 1200 r / min. In some preferred embodiments, the stirring time can be further shortened or extended to 20-60 min.
[0038] In some preferred embodiments, the filtration system specifically refers to filtering the uniformly mixed solution through a 0.5 micron filter bag and a 0.1 micron filter element.
[0039] In the specific embodiments of the present invention, the above-mentioned low-temperature wear-resistant resin is used as the prism material of the upper prism layer. The preparation method of the POP laminating film of the present invention is as follows: coating the resin on the PET base layer with a coating thickness of 20 to 30 μm, rolling out the required micro-prism structure, and then placing it at 700 mW / cm 2 The upper prism layer is prepared by curing the upper prism layer under ultraviolet irradiation with a power of 10s. The bottom surface of the PET base layer of the upper prism layer is bonded to the structural surface of the commercially available structural layer by a composite adhesive to finally obtain the POP laminating film, the structure of which is as follows: Figure 4 shown.
[0040] In a specific embodiment of the present invention, the prism pitch of the commercially available structural layer is 18 to 20 microns, and the height is 9 to 10 microns.
[0041] In a specific embodiment of the present invention, the preparation method of the low-temperature wear-resistant resin is specifically as follows: 30 parts of monomer ethoxylated bisphenol A diacrylate resin and 1 part of initiator 4-(phenylthio)phenyl diphenylsulfonium hexafluoroantimonate are added to a flask in sequence. Disperse at high speed of 1200r / min in a dark environment for 30 minutes, then continue to add 20 parts of the first type of acrylic resin o-phenylphenoxyethyl acrylic resin, 30 parts of the second type of acrylic resin phenol acrylic resin and 10 parts of oligomer polyurethane acrylic acid, heat to 30-40°C in a dark environment and continue to disperse at high speed of 1200r / min for 30 minutes. Finally, add 1 part of a slip agent, heat to 30-40°C and continue to disperse at high speed of 1200r / min for 60 minutes. After filtering the system, the low-temperature wear-resistant resin is obtained.
[0042] Example 1
[0043] This embodiment provides a POP laminating film, which is divided into two layers, namely, a structural layer (lower prism layer) and an upper prism layer from bottom to top, and the structural surface of the structural layer (lower prism layer) and the bottom surface of the upper prism layer are bonded by composite adhesive. The prisms of the upper prism layer are arranged in a row, and the pitch of the prisms is 18 to 20 microns; Figure 1 As shown, the cross section of the prism is a triangular structure with an arc-shaped top, the angle (R angle) corresponding to the arc is 88° to 90°, and the diameter of the corresponding circle is 0.5 to 1 micron. Figure 2As shown, the peak (prism peak) at the top of a single prism is composed of a number of hemispherical structures of different sizes arranged in a certain order, forming a special structure of staggered heights; Figure 3 The figure shows the side projection of the ridge peak, with a number of small hemispherical structures distributed between every two large hemispherical structures; wherein each large hemispherical structure has a span of 50 microns and a height of 5 microns; each small hemispherical structure has a span of 10 microns and a height of 1 micron; the spacing between each large hemispherical structure is 100 microns, and 100 microns = n*10 microns, where n is 10, i.e., 10 small hemispherical structures are arranged.
[0044] Example 2
[0045] This embodiment provides a POP laminating film, which is divided into two layers, namely, a structural layer (lower prism layer) and an upper prism layer from bottom to top, and the structural surface of the structural layer (lower prism layer) and the bottom surface of the upper prism layer are bonded by composite adhesive. The prisms of the upper prism layer are arranged in a row, and the pitch of the prisms is 26 to 28 microns; Figure 1 As shown, the cross section of the prism is a triangular structure with an arc-shaped top, the angle (R angle) corresponding to the arc is 88° to 90°, and the diameter of the corresponding circle is 0.5 to 1 micron. Figure 2 As shown, the peak (prism peak) at the top of a single prism is composed of a number of hemispherical structures of different sizes arranged in a certain order, forming a special structure of staggered heights; Figure 3 The figure shows the side projection of the ridge peak, with a number of small hemispherical structures distributed between every two large hemispherical structures; wherein each large hemispherical structure has a span of 100 microns and a height of 5 microns; each small hemispherical structure has a span of 50 microns and a height of 1 micron; the spacing between each large hemispherical structure is 250 microns, and 250 microns = n*50 microns, where n is 5.
[0046] Example 3
[0047] This embodiment provides a POP laminating film, which is divided into two layers, namely, a structural layer (lower prism layer) and an upper prism layer from bottom to top, and the structural surface of the structural layer (lower prism layer) and the bottom surface of the upper prism layer are bonded by composite adhesive. The prisms of the upper prism layer are arranged in a row, and the pitch of the prisms is 15 to 18 microns; Figure 1 As shown, the cross section of the prism is a triangular structure with an arc-shaped top, the angle (R angle) corresponding to the arc is 88° to 90°, and the diameter of the corresponding circle is 0.5 to 1 micron. Figure 2 As shown, the peak (prism peak) at the top of a single prism is composed of a number of hemispherical structures of different sizes arranged in a certain order, forming a special structure of staggered heights; Figure 3Shown is a side projection of the ridge peak, with several small hemispherical structures distributed between every two large hemispherical structures; wherein, each large hemispherical structure has a span of 500 microns and a height of 10 microns; each small hemispherical structure has a span of 100 microns and a height of 2 microns; the spacing between each large hemispherical structure is 1000 microns, and 1000 microns = n*100 microns, where n is 10.
[0048] Test Example 1
[0049] A common POP laminating film was prepared, and the upper prism layer of Example 1 was replaced by a commercially available structural layer, and the rest was the same as Example 1.
[0050] Test method: 1) Place the POP laminated film to be tested upside down on the polarizer and place the whole in a low temperature environment of -40℃ for 30 minutes; 2) Press a weight on the POP, then pull the POP to make it slide and rub on the polarizer, and pull it back and forth three times; 3) Use a strong flashlight to check whether there are scratches on the surface of the polarizer. If there are scratches, reduce the weight; if there are no scratches, continue to increase the weight until scratches appear.
[0051] The test results are shown in Table 1. The POP laminating film using the new structure and low-temperature wear-resistant resin as the material can significantly reduce the wear of the polarizer in the low-temperature environment of POP.
[0052] Table 1
[0053]
[0054] Test Example 2
[0055] A common POP laminating film was prepared, and a commercially available structural layer was used to replace the upper prism layer of Example 1, and the rest was the same as Example 1. When the common POP laminating film was used to assemble a liquid crystal display screen, it was easy to interfere with the screen pixels to form long strip interference fringes. The schematic diagram of the interference effect is shown in Figure 5 .
[0056] The POP laminating film of Example 1 of the present invention can significantly reduce the generation of interference fringes. The schematic diagram of the interference effect is shown in FIG. Figure 6 .
[0057] Comparative Example 1. DOP laminating film
[0058] like Figure 7As shown in the figure, the DOP laminating film is divided into two layers, the upper surface is the diffusion particles, which play the role of atomization and shielding; the lower layer is a prism structure, which plays the role of focusing. The upper surface of the DOP laminating film is composed of small beads with a diameter of 2-30um randomly stacked, with ups and downs, and the protruding parts are spherical. After the DOP laminating film is assembled, when the diffusion particles come into contact with the polarizer under the LCD screen, the surface is a spherical structure (smooth), the friction is small, and it is not easy to wear the polarizer. The diffusion particles on the DOP surface are randomly arranged, and it is not easy to form moiré interference fringes with the liquid crystal pixels.
[0059] Comparative Example 2. MOP Lamination Film
[0060] like Figure 8 As shown, the MOP laminating film is divided into two layers, the upper surface is a hemispherical microlens structure, which plays a role of shielding and focusing; the lower layer is a prism structure, which plays a focusing role. The upper surface of the MOP laminating film is a hemispherical microlens structure (diameter 20-50um). After the MOP laminating film is assembled, the microlens structure on the surface contacts the polarizer (smooth), with low friction, and it is not easy to scratch the polarizer. The microlens structure on the surface of the MOP laminating film is arranged in a honeycomb shape, staggered from each other, and it is not easy to form moiré interference fringes with liquid crystal pixels.
[0061] Compared with the embodiment of the present invention, the brightness of DOP laminating film and MOP laminating film is lower. On some TV models with high requirements for energy consumption control, the brightness of the TV cannot meet the requirements. Under the same architecture, the brightness of DOP and MOP is 10-20% lower than that of POP.
[0062] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For the technical personnel in this field, the present invention can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made to the present invention should be included in the protection scope of the present invention.
Claims
1. An anti-interference, low-temperature and wear-resistant POP laminating film, characterized in that: The POP laminating film is divided into two layers, namely a structural layer and an upper prism layer from bottom to top, and the structural surface of the structural layer and the bottom surface of the upper prism layer are bonded by composite adhesive; The prisms of the upper prism layer are arranged in a row, and the cross section of the prism is a triangular structure with an arc-shaped top; the prism peak of a single prism of the upper prism layer is composed of a number of hemispherical structures of different sizes arranged in a certain order; The structure is arranged in layers with prisms that are triangular in cross section.
2. The POP laminating film according to claim 1, characterized in that: The prism spacing of the upper prism layer is 15 to 28 microns; the height of the prism is half of the prism spacing, which is 7 to 14 microns.
3. The POP laminating film according to claim 2, characterized in that: The prism pitch of the upper prism layer is 18 to 20 microns, and the prism height is 9 to 10 microns.
4. The POP laminating film according to claim 1, characterized in that: The angle corresponding to the top arc of the cross section of the prism-like triangular structure is 88° to 90°, and the diameter of the corresponding circle is 0.5 to 1 micrometer.
5. The POP laminating film according to claim 1, characterized in that: The structure of the prism peak is specifically that a number of small hemispherical structures are distributed between every two large hemispherical structures; the span of each large hemispherical structure is A and the height is D; the span of each small hemispherical structure is C and the height is 1 / 5D; the spacing between each large hemispherical structure is B, and B=n*C, where n is a positive integer; A is preferably 50 to 500 microns; D is preferably 5 to 10 microns; C is preferably 10 to 100 microns; and n is a positive integer of 5 to 10.
6. The POP laminating film according to claim 1, characterized in that: The prisms of the upper prism layer are made of low-temperature wear-resistant resin and are prepared from the following components in parts by weight: 5-10 parts of ethoxylated bisphenol A diacrylate resin and 25-30 parts of 4-(phenylthio)phenyl diphenylsulfonium hexafluoroantimonate are dispersed at a high speed of 500-2000 r / min in a dark environment for 30 minutes, then 15-20 parts of the first type of acrylic resin, 25-30 parts of the second type of acrylic resin and 5-10 parts of polyurethane acrylic or epoxy acrylic resin are added, heated to 30-40°C in a dark environment and dispersed at a high speed of 500-2000 r / min for 30 minutes, finally 0.5-1 part of a slip agent is added, heated to 30-40°C and dispersed at a high speed of 500-2000 r / min for 60 minutes, and a low-temperature wear-resistant resin is obtained after passing through a filtration system.
7. The POP laminating film according to claim 6, characterized in that: The first type of acrylic resin is o-phenylphenoxyethyl acrylic resin or ethoxylated o-phenylphenoxyethyl acrylic resin, and the second type of acrylic resin is phenol acrylic resin or ethoxylated phenol acrylic resin.
8. The POP laminating film according to claim 6, characterized in that: The stirring speed of the high-speed dispersion is preferably 1200 r / min.
9. The POP laminating film according to claim 6, characterized in that: The filtration system specifically refers to filtering the uniformly mixed solution through a 0.5 micron filter bag and a 0.1 micron filter element.
10. Use of the POP laminating film according to any one of claims 1 to 9 in preparing a liquid crystal display screen.